1987
DOI: 10.1002/1097-0142(19871215)60:12<2873::aid-cncr2820601204>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Antimammary carcinogenic activity of 17-alpha-ethinyl estriol

Abstract: Both initiation and promotion of dimethylbenz(a)anthracene (DMBA)-induced mammary carcinogenesis were inhibited by prophylactic therapy for 1 to 7 months using 17-alpha-ethinyl-estriol in doses as low as 1.0 microgram/d administered to intact virgin female Sprague-Dawley rats at 35 to 65 days of age. Administration of 638-micrograms single or multiple doses 2 to 3 weeks before DMBA induced a 75% to 85% reduction in cancer incidence after 1 year (P less than 0.001). When treatment was begun 2 weeks after DMBA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The growth of DMBA-induced tumors is dependent on estrogens and prolactin [26] . Ovariectomy, as a means of suppressing endogenous levels of estrogens, synthetic estrogens [27] , natural estrogens [28 -30] , tibolone [31] , anti-estrogen treatment [32,33] , androgens [34] , progestogens [31,35,36] , selective progesterone receptor modulators [37] , GnRH analogues [32,38] and aromatase-inhibitors [39] have all been investigated in the DMBA mammary tumor model.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of DMBA-induced tumors is dependent on estrogens and prolactin [26] . Ovariectomy, as a means of suppressing endogenous levels of estrogens, synthetic estrogens [27] , natural estrogens [28 -30] , tibolone [31] , anti-estrogen treatment [32,33] , androgens [34] , progestogens [31,35,36] , selective progesterone receptor modulators [37] , GnRH analogues [32,38] and aromatase-inhibitors [39] have all been investigated in the DMBA mammary tumor model.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of antibodies to AFP (but not to gonadotropin) neutralized the proliferation-inhibiting effect of AFP-containing media. Jacobson therefore proposed a unified mechanism for the reduction of breast cancer risk by the hormones of pregnancy (42), namely that neither estradiol, estriol, progesterone nor chorionic gonadotropin is the proximal inhibitor of breast cancer as had been asserted (43)(44)(45)(46)(47) but rather that these agents act on the liver to elicit production of AFP and that AFP is the proximal mediator of reduction of breast cancer risk. The conclusion is that in the treatment of carcinogen-exposed rats with the hormones of pregnancy and by inference in women who have experienced pregnancy, AFP is the proximal agent that inhibits breast cancer.…”
Section: Laboratory Observationsmentioning
confidence: 60%
“…Many of these agents had been shown to decrease incidence of breast cancer when administered to carcinogen-exposed rats. Serial injections into carcinogen-exposed animals of either estriol (43)(44)(45), estrogen together with progesterone (46), or human chorionic gonadotropin (47) decreased the incidence of mammary cancer compared with carcinogen-exposed animals not treated with those hormones of pregnancy. Seemingly, a number of different pregnancy-associated endocrine substances are effective surrogates for parity in terms of reducing mammary cancer risk, but there had been no reasonable explanation of why these diverse treatments should lead to the same outcome.…”
Section: Laboratory Observationsmentioning
confidence: 99%
“…In every case, we used MNU, although in some of the previous investigations, DMBA was used (7,8,13,17,18 Controls. The no-treatment group consisted of 30 female rats exposed to MNU without subsequent treatment, and experienced the maximal number of tumors over the course of the ensuing 4 mo.…”
Section: Hormone Treatmentsmentioning
confidence: 99%
“…This is an obvious and striking parallel to the effect of parity on human breast cancer risk (4). Users of these rat models have supplanted for pregnancy in rats serial injections of test substances such as E 3 (6,17,18), E 2 together with P (5), or hCG (8), and found that the number of induced cancers was significantly below that found in rats not treated with these hormones of pregnancy. It seems that in rats, a number of different pregnancy-associated endocrine substances are effective surrogates for parity in terms of the reduction of mammary cancer risk.…”
Section: Introductionmentioning
confidence: 99%